A fuzzy cognitive map approach for effect-based operations: An illustrative case - Yaman, Dilek; Polat, Seçkin (Elsevier BV, 2009)
This paper proposes the use of fuzzy cognitive maps (FCMs) as a technique for supporting the decision-making process in effect-based planning. The goal is to determine alternative courses of action to realize the aims of an operation, and choose the best option among them. With adequate consideration of the problem features and the constraints governing the method used, an FCM is developed to model effect-based operations (EBOs). In this study, certain features that do not exist in the classical FCM method were added to our FCM concept value calculation algorithm; these include influence possibility, influence duration, dynamic influence value-changing, and influence permanence. The model developed was applied to an illustrative scenario involving military planning, and we comment on the usefulness of the proposed methodology.